2008
DOI: 10.4269/ajtmh.2008.78.895
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics and Phylogeography of Aedes aegypti (Diptera: Culicidae) from Brazil

Abstract: Population genetic analyses were conducted using samples of Aedes aegypti from 14 localities in the north, southeast, northeast, and central regions of Brazil. An 852-bp region of the mitochondrial DNA cytochrome oxidase I (COI) gene was used in the analyses. Ten haplotypes were observed, and cluster analyses revealed 2 groups (lineages) separated by 8 fixed mutations, suggesting that the Brazilian Ae. aegypti populations probably came from East and West Africa, with evidence of multiple introductions, one rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
42
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 50 publications
10
42
1
8
Order By: Relevance
“…However, with advances in molecular biology, numerous studies have demonstrated that morphological keys are not sufficient. In addition, they are accompanied with several limitations (9) which might be due to several reasons, such as, minor genetic variation due to ecological impact, as well as, the constant use of insecticides, in addition to others factors (10)(11)(12). Therefore, numerous molecular researches have been undertaken to find new molecular marker as an alternative tool to identify mosquito species.…”
mentioning
confidence: 99%
“…However, with advances in molecular biology, numerous studies have demonstrated that morphological keys are not sufficient. In addition, they are accompanied with several limitations (9) which might be due to several reasons, such as, minor genetic variation due to ecological impact, as well as, the constant use of insecticides, in addition to others factors (10)(11)(12). Therefore, numerous molecular researches have been undertaken to find new molecular marker as an alternative tool to identify mosquito species.…”
mentioning
confidence: 99%
“…Esses genes têm sido utilizados recentemente em análise de genética populacional, identificação de espécies crípticas, filogenia e filogeografia de diversos grupos da família Culicidae (Bracco et al, 2007;Caldera et al, 2013;de Lourdes Muñoz et al, 2013;Lorenz et al, 2014;Moore et al, 2013;Paduan, Martins Ribolla, 2008;Petersen et al, 2015;Sallum et al, 2002;Scarpassa et al, 2008;Scarpassa, Conn, 2007;Werblow et al, 2014;Zawani et al, 2014).…”
Section: O Gene Coi (Citocromo Oxidase Subunidade I) E O Gene Nd4 (Niunclassified
“…aegypti (Bracco et al, 2007;da Costa-da-Silva et al, 2005;Gorrochotegui-Escalante et al, 2002;Herrera et al, 2006;Jaimes-Dueñez et al, 2015;Moore et al, 2013;Paupy et al, 2012), inclusive no Brasil (Lima Júnior, Scarpassa, 2009;Scarpassa et al, 2008). A espécie Ae.…”
Section: O Gene Coi (Citocromo Oxidase Subunidade I) E O Gene Nd4 (Niunclassified
See 1 more Smart Citation
“…Devido a essas características, o genoma mitocondrial tem sido usado como marcador molecular em estudos de genética de populações, tais como fluxo gênico, tamanho efetivo das populações e história evolutiva (Spanos et al, 2000). O gene Citocromo oxidase, subunidade I, é amplamente usado em investigações de estrutura populacional de insetos como ilustrado por Scarpassa et al (2008) que analisou o gene COI para caracterizar 14 populações de Aedes aegypti no norte, nordeste, sudeste e centro-oeste do Brasil, resultando em duas linhagens diferentes, provavelmente vindas do leste e oeste da África.…”
Section: Espécies Crípticasunclassified